AGRARIAN SECTOR OF THE REPUBLIC OF UZBEKISTAN IN A WAY OF DEVELOPMENT AND FEATURES OF ENTERPRISE ACTIVITY - Rashid Khakimov; Samiyeva Gulnoza Toxirovna (International Journal on Orange Technologies, 2020)
In the given scientific article it is spoken about how in Uzbekistan pays attention to the development of agrarian sector as carrying out reforms within independence. And also, in article appreciable structural and indicative shifts in sphere of agricultural productions by the help farmer and agriculturalist facilities. Pays attention to special economic parameters which carry out agriculture facilities.